Fragmentation-based dynamic size effect of layered roller compacted concrete (RCC) under impact loadings. (20th December 2018) - Wang, Xiao-hua; Zhang, She-rong; Wang, Chao; Song, Ran; Shang, Chao; Cao, Ke-lei
Highlights: Dynamic size effect of RCC has been verified based on the fragment size distribution. Dynamic behaviors of RCC is tightly related to the fragment composition. Fractal dimension of fragments is size-dependent and strain-rate sensitive. Fragmentation-based fractal concept is suggested to evaluate dynamic behaviors of RCC. Abstract: For further investigating the dynamic size effect of roller compacted concrete (RCC), this paper focuses on the concrete fragmentation under impact loadings, which compensates the one-sidedness of pure strength and deformation analysis. 101 RCC specimens with different size have been prepared and tested under impact loadings. Then, more comprehensive understandings on size-dependence and strain-rate sensitivity of dynamic behaviors for RCC can be obtained in terms of failure process, fragment size distribution, and fractal characteristics. The experimental results indicate that the dynamic fragmentation process is highly related to the multiaxial stress state in the specimens. The fragment size distribution can be used to depicture the dynamic behaviors of RCC, indicating the tight correlation among crack propagation, energy dissipation and failure strength. The suggested exponential growth models, interpreting dynamic compressive strength and toughness with fractal dimension, provide an effective way to evaluate the dynamic behaviors of RCC based on the fragment size distribution.